The Influence of Cluttering, Work Environment, and Implementation of the 5-S Methods on the Performance of Coal Mining Employees - Rizky, Yulfani Akhmad; Khuzaini, Khuzaini; Shaddiq, Syahrial; Noor, Ihsan; Syahid, Muhammad (Technium Social Sciences Journal, 2023)
The availability of goods and spare part to support mining operations is depends on how to manage the storage of these goods in the warehouse at site. Warehouse management depends on the arrangement of goods placement. An excessive pile of items that are not well managed becomes a negative impact for the work environment. More goods stored in the warehouse with uncontrolled with clutter condition will disrupt employee working conditions then impacted of a failure working order interprets. The 5-S concept implementation is a method of decluttering by S1 is seiri (concise), S2 is seiton (neat), S3 is seiso (clean), S4 is seiketsu (control), and S5 is shitsuke (diligent) to improve material handling in the store to have better condition of working environmental for better employee performance in the warehouse. As a journal review of the 5-S concept, can be summarized that the 5-S concept implementation in a mining operation organization have a positive significant effect to their working performance including time, and cost efficiency.